2021
DOI: 10.1073/pnas.2018731118
|View full text |Cite
|
Sign up to set email alerts
|

A single historical substitution drives an increase in acetylcholine receptor complexity

Abstract: Human adult muscle-type acetylcholine receptors are heteropentameric ion channels formed from four different, but evolutionarily related, subunits. These subunits assemble with a precise stoichiometry and arrangement such that two chemically distinct agonist-binding sites are formed between specific subunit pairs. How this subunit complexity evolved and became entrenched is unclear. Here we show that a single historical amino acid substitution is able to constrain the subunit stoichiometry of functional acetyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 55 publications
2
33
1
Order By: Relevance
“…All CCT subunits inherited an oligomeric interface from an ancient, single-copy CCT gene that duplicated several times deep in the eukaryotic lineage 54 . In many paralogs that interface was likely only partly lost as their specific positions in the ring were entrenched, as has been demonstrated for other multimeric complexes with ring topologies 55,56 . Our results could be explained if the residual affinity between paralogs that are not adjacent in TRiC reflects incomplete loss of ancient contacts 7,17,[47][48][49] .…”
Section: Discussionmentioning
confidence: 79%
“…All CCT subunits inherited an oligomeric interface from an ancient, single-copy CCT gene that duplicated several times deep in the eukaryotic lineage 54 . In many paralogs that interface was likely only partly lost as their specific positions in the ring were entrenched, as has been demonstrated for other multimeric complexes with ring topologies 55,56 . Our results could be explained if the residual affinity between paralogs that are not adjacent in TRiC reflects incomplete loss of ancient contacts 7,17,[47][48][49] .…”
Section: Discussionmentioning
confidence: 79%
“…A concatameric construct confirmed that the two β Anc subunits resided next to each other, occupying positions in the heteropentameric complex usually reserved for the human β- and δ-subunits (Fig. 1) (7). Regardless of whether they bind agonist or not, all pLGIC subunits have both principal (+) and complementary (−) subunit interfaces.…”
Section: Introductionmentioning
confidence: 70%
“…We therefore wondered if the ability of β Anc to form spontaneously opening homomers was an artefact of the discordant tree used to reconstruct it. To test this, we took advantage of an alternate ancestral β-subunit, called “β AncS ”, whose reconstruction was based upon a molecular phylogeny that matched the accepted species phylogeny (7). Despite 67 substitutions and 6 indels relative to β Anc , when expressed alone, β AncS still formed homomeric channels that opened in bursts in the absence of acetylcholine (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations